Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1002/we.1524
|View full text |Cite
|
Sign up to set email alerts
|

US East Coast offshore wind energy resources and their relationship to peak‐time electricity demand

Abstract: This study characterized the annual mean US East Coast (USEC) offshore wind energy (OWE) resource on the basis of 5 years of high‐resolution mesoscale model (Weather Research and Forecasting–Advanced Research Weather Research and Forecasting) results at 90 m height. Model output was evaluated against 23 buoys and nine offshore towers. Peak‐time electrical demand was analyzed to determine if OWE resources were coincident with the increased grid load. The most suitable locations for large‐scale development of OW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 43 publications
2
42
0
Order By: Relevance
“…2 In addition to the research and development of such wind turbines, offshore wind resource assessment techniques based on satellite remote sensing 3,4 and mesoscale meteorological models [5][6][7][8] that are less dependent on in situ measurements have also been studied to reduce the technical and financial constraints of siting meteorological observation masts offshore.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 In addition to the research and development of such wind turbines, offshore wind resource assessment techniques based on satellite remote sensing 3,4 and mesoscale meteorological models [5][6][7][8] that are less dependent on in situ measurements have also been studied to reduce the technical and financial constraints of siting meteorological observation masts offshore.…”
Section: Introductionmentioning
confidence: 99%
“…As offshore wind power generation is rapidly extending all over the world, 1 feasibility studies not only on the bottom-fixed wind turbines in shallow water but also on the floating wind turbines in deep water have been conducted. 2 In addition to the research and development of such wind turbines, offshore wind resource assessment techniques based on satellite remote sensing 3,4 and mesoscale meteorological models [5][6][7][8] that are less dependent on in situ measurements have also been studied to reduce the technical and financial constraints of siting meteorological observation masts offshore. Mesoscale meteorological models are a promising tool for regional-scale site assessments, 9 since they can simulate offshore wind fields with high spatial and temporal resolutions while taking into account large and local-scale meteorological phenomena by using objective analyses for their boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Source: (Dvorak et al, 2013). 25 (Dvorak et al, 2013). 26 According to a 2013 Stanford University study on wind resources and correlation with peak demand hours.…”
Section: Installed Global Capacity By Marketmentioning
confidence: 99%
“…26 According to a 2013 Stanford University study on wind resources and correlation with peak demand hours. (Dvorak et al, 2013). 27 Offshore transmission cables can eliminate the burden of building new terrestrial cables; this has been shown to be a limiting factor for land-based wind turbines.…”
Section: Installed Global Capacity By Marketmentioning
confidence: 99%